2017
DOI: 10.1371/journal.pone.0179450
|View full text |Cite
|
Sign up to set email alerts
|

Activation of complement factor B contributes to murine and human myocardial ischemia/reperfusion injury

Abstract: The pathophysiology of myocardial injury that results from cardiac ischemia and reperfusion (I/R) is incompletely understood. Experimental evidence from murine models indicates that innate immune mechanisms including complement activation via the classical and lectin pathways are crucial. Whether factor B (fB), a component of the alternative complement pathway required for amplification of complement cascade activation, participates in the pathophysiology of myocardial I/R injury has not been addressed. We ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 132 publications
0
26
0
Order By: Relevance
“…Studies in other models of inflammatory and immune disease have shown close correlation between the accumulation of C3d, the duration of ischaemia and tissue infarction 5 , 6 . Moreover, there are numerous pre-clinical and clinical studies that demonstrated involvement of Complement and in particular C3d in myocardial reperfusion injury 8 11 . As a clinical assay, complement measurement in blood, urine and tissue biopsy samples is widely used as a biomarker for many clinical conditions 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies in other models of inflammatory and immune disease have shown close correlation between the accumulation of C3d, the duration of ischaemia and tissue infarction 5 , 6 . Moreover, there are numerous pre-clinical and clinical studies that demonstrated involvement of Complement and in particular C3d in myocardial reperfusion injury 8 11 . As a clinical assay, complement measurement in blood, urine and tissue biopsy samples is widely used as a biomarker for many clinical conditions 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that the complement system is an important participant in the pathophysiological process of myocardial I/R injury 6,17,18 . Conversely, inhibiting complement system activation can significantly reduce myocardial I/R injury and myocardial infarct size [19][20][21] .…”
Section: ■ Discussionmentioning
confidence: 99%
“…In response to myocardial injury, the complement cascade is activated and initiates an inflammatory response involving the recruitment of polymorphonuclear leukocytes and the release of inflammatory cytokines. Indeed, the excessive activation of the complement and its products C3 and C5a play an important role in myocardial necrosis during myocardial I/R 5,6 . Moreover, the generation of the anaphylatoxins C3 and C5a further activates the c-Jun N-terminal kinase (JNK) signaling to aggravate inflammatory response 7 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chun et al. also reported that complement factor B (CFB) from circulation contributed to myocardial necrosis in ischemia/reperfusion‐treated mice and its deficiency would remarkably limit the injury . It is well known that cardiac remodeling (CR), in which immunological factors play a key role, is the pathological basis of heart failure in patients with ESRD .…”
Section: Introductionmentioning
confidence: 99%
“…Coan et al discovered that Cfb −/− rats manifested lower blood pressure, increased ejection fraction and fractional shortening, and reduced left ventricular mass [16]. Chun et al also reported that complement factor B (CFB) from circulation contributed to myocardial necrosis in ischemia/reperfusion-treated mice and its deficiency would remarkably limit the injury [17]. It is well known that cardiac remodeling (CR), in which immunological factors play a key role, is the pathological basis of heart failure in patients with ESRD [18].…”
Section: Introductionmentioning
confidence: 99%